Dynamic characteristics of light emission accompanying cryocondensation of nitrous oxide and ethanol - Drobyshev, A.; Aldiyarov, A.; Korshikov, E.; Strzhemechny, Y.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
We report new results in the study of cryoradiation accompanying the condensation of some gas. The main objectives of this research are: (i) check a broader range of substances for their ability to cryoradiation; (ii) the study of the nature of radiation and its relaxation characteristics; (iii) the study of thermally stimulated processes in condensed samples. Of the compounds tested only nitrous oxide and ethanol exhibited the ability to generate cryoradiation during condensation from the gas phase. Separate flashes detected by a photomultiplier represent a superposition of a series of successive relaxation processes of individual regions, somehow related to each other. It is possible that such areas are crystallites containing a set of molecules of nitrous oxide/ethanol, which are in metastable states with different activation energies. Radiation by these molecules during the transition into the ground state induces successive relaxation processes of molecular groups according to their activation energy distributions. Nonequilibrium radiative states forming in the process of cryocondensation of nitrous oxide and ethanol may have different nature of the activation energy distribution and this could explain the difference in the character of the radiation relaxation in these substances.